Fodor's essential Spain 2026 - Askham, Gemma; Ferrarese, Marco, 1980-; Kemper, Benjamin; Lloyd, Megan Frances; Rodriguez, Emmanuel; Styles, Joanna (Fodor's travel guides., 2026)
"Whether you want to explore the Alhambra, marvel at La Sagrada Familia, or enjoy tapas, wine, and flamenco, the local Fodor's travel experts in Spain are here to help! Fodor's Essential Spain guidebook is packed with maps, carefully curated recommendations, and everything else you need to simplify your trip-planning process and make the most of your time. This new edition has been fully-redesigned with an easy-to-read layout, fresh information, and beautiful color photos"--